Development of a mosaic-type array formed by Si photodiodes for charged-particle detection in heavy-ion collisions - Li Jiatai; Imai Nobuaki; Yokoyama Rin; Kojima Reiko; Michimasa Shin’ichiro; Chillery Thomas; Hanai Shutaro; Kitamura Noritaka; Saito Takeshi; Suzuki Daisuke; Nishimura Daiki; Takada Eiichi; et al. (EPJ Web of Conferences, 2024)
Silicon (Si) detectors find widespread application in heavy-ion collisions. In order to achieve a position-sensitive charged-particle detection with a relatively low cost, we have developed a mosaic-type array based on off-the-shelf Si photodiodes (Hamamatsu S13955-01). Its high modularity allows one to modify the geometric configuration of the array according to specific experimental requirements. In this contribution, characteristics of the photodiode tested with α source and experimental results of the α-decay spectroscopy are presented.